2000
DOI: 10.2337/diabetes.49.6.1016
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes downregulates GLUT1 expression in the retina and its microvessels but not in the cerebral cortex or its microvessels.

Abstract: Capillaries in the retina are more susceptible to develop microvascular lesions in diabetes than capillaries in the embryologically similar cerebral cortex. Because available evidence implicates hyperglycemia in the pathogenesis of diabetic retinopathy, differences in glucose transport into the retina and brain might contribute to this observed tissue difference in susceptibility to diabetes-induced microvascular disease. Thus, we compared levels of GLUT1 and GLUT3 expression in the retina, cerebrum, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
2
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 46 publications
7
59
2
1
Order By: Relevance
“…Apoptotic cell death is initiated in a very few photoreceptors about one month after the onset of diabetes, and accelerates from three months onwards. Thus, the main causal factor for the apoptosis in the ONL is not likely to be directly associated with altered glucose metabolism and consequent altered vascular conditions, as supported by another report [15,29]. They describe that the main glucose transporter in the retina, GLT-1, is much more strongly expressed in the pigment epithelium than in the neural retina or its microvessels.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Apoptotic cell death is initiated in a very few photoreceptors about one month after the onset of diabetes, and accelerates from three months onwards. Thus, the main causal factor for the apoptosis in the ONL is not likely to be directly associated with altered glucose metabolism and consequent altered vascular conditions, as supported by another report [15,29]. They describe that the main glucose transporter in the retina, GLT-1, is much more strongly expressed in the pigment epithelium than in the neural retina or its microvessels.…”
Section: Discussionsupporting
confidence: 53%
“…GLT-1 in the epithelium is less affected or completely unaffected by diabetes. However, whether the regulatory mode of the GLT-1 in the neural retina in response to diabetes is upregulation [29] or downregulation [18,30], is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Potential changes in the expression of glucose transporters, although not studied by our group, have been examined previously (35). It has been demonstrated that endothelial cells (except retinal endothelium) are unable to downregulate the expression of glucose transporters in hyperglycemia and therefore remain continuously exposed to the elevated glucose influx and oxidant stress (36,37,38). These data collectively indicate that preexisting endothelial dysfunction may modify cell responsiveness to VEGF and that VEGF under these circumstances becomes insufficient for angiogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…The accumulation of AGEs and glucose in the retina has been associated with other conditions of hyperglycemia, notably diabetic retinopathy, and some of the phenotypes noted in this work, such as RPE thinning, RPE vacuolation, photoreceptor degeneration, and thinning of the inner retinal layer, were also observed in humans and experimental models of diabetic retinopathy (33,(53)(54)(55)(56)(57)(58)(59). Glycation results in the dysfunction of structural proteins and impaired protein-editing machineries, including autophagy and the ubiquitin proteolytic systems, functions that are required for the degradation of phagosomes and AGEs (11,29,60).…”
Section: Discussionmentioning
confidence: 86%